2021
DOI: 10.1093/migration/mnab037
|View full text |Cite
|
Sign up to set email alerts
|

Shoring up economic refugees: Venezuelan migrants in the Ecuadoran labor market

Abstract: Ecuador became the third largest receiver of the 4.3 million Venezuelans who left their country in the last five years, hosting around 10 per cent of them. Little is known about the characteristics of these migrants and their labor market outcomes. This article fills this gap by analyzing a new large survey (EPEC). On average, Venezuelan workers are highly skilled and have high rates of employment, compared with Ecuadorans. However, their employment is of much lower quality, characterized by low wages, and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“… 4 The studies by Shamsuddin et al (2021) and Olivieri et al (2021b) for Brazil and Ecuador, respectively, are the closest to ours within the region. Our work also relates to recent studies, such as Angelini et al (2015), Basilio et al (2017), and Brell et al (2020), on the integration of forced migrants.…”
mentioning
confidence: 64%
See 3 more Smart Citations
“… 4 The studies by Shamsuddin et al (2021) and Olivieri et al (2021b) for Brazil and Ecuador, respectively, are the closest to ours within the region. Our work also relates to recent studies, such as Angelini et al (2015), Basilio et al (2017), and Brell et al (2020), on the integration of forced migrants.…”
mentioning
confidence: 64%
“…Similarly, most of the studies on the Venezuelan migration in Latin America focus on the effects of immigrants on the economic conditions of natives. For Ecuador, Olivieri et al (2021a) find that natives with lower levels of education have experienced an increase in their unemployment rates, in regions with a high influx of migrants. For Colombia, Caruso, Canon and Mueller (2019) and Lebow (2022) find a negative effect of the labor supply shock on wages in urban areas and for less educated natives.…”
Section: Related Literaturementioning
confidence: 95%
See 2 more Smart Citations
“…For the Syrian refugee crisis, there is little evidence of impacts in neighboring countries' labor markets (Tumen, 2016;Fallah et al, 2019;David et al, 2020). Studies on the Venezuelan exodus showed no significant effects on the labor market in Colombia (Bonilla-Mejía et al, 2020;Santamaria, 2020) and Ecuador (Olivieri et al, 2021). Bahar et al (2021) study the labor market impacts of an extensive migratory amnesty program that granted work permits to nearly half a million undocumented Venezuelan migrants in Colombia in 2018.…”
Section: Introductionmentioning
confidence: 99%